Non-invasive Assessment of Vaccine-Induced HPV Antibodies via First-Void Urine - Pattyn, Jade; Van Keer, Severien; Téblick, Laura; Van Damme, Pierre; Vorsters, Alex (Frontiers in Immunology, 2020)
The potential of first-void (FV) urine as a non-invasive method to monitor human papillomavirus (HPV) vaccination has been reported, mainly focusing on urine as a sample to assess HPV DNA. Besides HPV DNA, vaccine-induced HPV antibodies originating from cervicovaginal secretions were recently shown to be detectable in FV urine as well. This presents a novel opportunity for non-invasive sampling to monitor HPV antibody status in women participating in large epidemiological studies and HPV vaccine trials. The simultaneous assessment of both HPV infection and immunogenicity on a non-invasive, readily obtained sample is particularly attractive.